Новый алмазный породоразрушающий инструмент - Осецкий, А.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
In the article new diamond core bits are described developed in last years. Results of application of diamond core bits and reamers in various – geological conditions are presented.